In vivo embryo development in bitches inseminated laparoscopically after ovulation time estimated based on a single progesterone determination - Alves, Aracelle Elisane; Motheo, Tathiana Ferguson; Apparicio, Maricy Ferreira [UNESP]; Mostachio, Giuliano Queiroz; dos Santos, Ricarda Maria; Vicente, Wilter Ricardo Russiano [UNESP]; Luvoni, Gaia Cecilia (FapUNIFESP (SciELO), 2023)
Logistic and economical limitations are often the causes of dog owners not accurately monitoring the estrous cycle and the optimal insemination time. The aim of this study was to evaluate in vivo early embryonic development in bitches, after the analysis of sequential vaginal cytologies associated to single progesterone measurement and single laparoscopic insemination with high quality semen (fresh and with high spermatozoa concentration) or low-quality semen (frozen/thawed and with low spermatozoa concentration) at 48 h post-ovulation time predicted on a single progesterone measurement. Ten bitches were inseminated with 250 x 106 fresh spermatozoa (80% motility), and ten with 80 x 106 frozen/thawed spermatozoa (60% motility) in the cranial part of each uterine horn. Seven days later, ovariohysterectomy was performed and the oviducts and uterine horns and body were flushed to recover embryos and unfertilized oocytes. In 80% of the bitches inseminated with fresh and 50% of bitches inseminated with frozen/thawed semen, embryos at 2 to 8 cells stage were recovered mostly from the, oviducts. This study indicates that pregnancies can be obtained with a single laparoscopic intrauterine insemination after single serum progesterone measurement, although with a low number of embryos. This result should be taken into account in case economic or logistic restrictions that affect the possibility of owners to plan an accurate monitoring of the optimal breeding time using fresh and frozen semen.
Keywords: bitches; embryo development; Intrauterine artificial insemination